2008
DOI: 10.1175/2007jpo3906.1
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Coupling in Baroclinically Unstable Flows

Abstract: A two-layer quasigeostrophic model in a channel is used to study the influence of lateral displacements of regions of different sign mean potential vorticity gradient (⌸ y ) on the growth rate and structure of linearly unstable waves. The mean state is very idealized, with a region of positive ⌸ y in the upper layer and a region of negative ⌸ y in the lower layer; elsewhere ⌸ y is zero. The growth rate and structure of the model's unstable waves are quite sensitive to the amount of overlap between the two regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Previous observations have shown that the density structure of the overflow water in Denmark Strait is consistent with that of hydraulic flow over a sill (e.g., Spall and Price 1998;Nikolopoulos et al 2003). Using observations and a numerical model, Käse et al (2003) diagnosed the hydraulic conditions in Denmark Strait using the local Froude number Fr 5 y/ ffiffiffiffiffiffiffiffi g 0 D p , where y is the flow speed, D is the vertical length scale, g 0 5 gDr/r is the reduced gravity, g is the gravitational acceleration, and Dr is the density difference across the interface.…”
Section: A Hydraulic Criticalitysupporting
confidence: 54%
See 1 more Smart Citation
“…Previous observations have shown that the density structure of the overflow water in Denmark Strait is consistent with that of hydraulic flow over a sill (e.g., Spall and Price 1998;Nikolopoulos et al 2003). Using observations and a numerical model, Käse et al (2003) diagnosed the hydraulic conditions in Denmark Strait using the local Froude number Fr 5 y/ ffiffiffiffiffiffiffiffi g 0 D p , where y is the flow speed, D is the vertical length scale, g 0 5 gDr/r is the reduced gravity, g is the gravitational acceleration, and Dr is the density difference across the interface.…”
Section: A Hydraulic Criticalitysupporting
confidence: 54%
“…Almansi et al (2020) have shown that the surges in transport result in the generation of cyclones downstream of the sill. These are the well-known ''DSOW cyclones'' that emanate from the strait and propagate southward along the East Greenland continental slope (Bruce 1995;Spall and Price 1998;von Appen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A necessary condition for baroclinic instability is that the cross-stream gradient of Ertel potential vorticity (PV) changes sign with depth (e.g. Spall and Pedlosky, 2008). Ertel PV Π is defined as…”
Section: Baroclinic Instabilitymentioning
confidence: 99%
“…It is of interest to consider the potential vorticity structure of the flow in Barrow Canyon for the pumping scenario. The Ertel potential vorticity (Π) can be written as (Pickart, Torres, & Fratantoni, 2005;Spall & Pedlosky, 2008):…”
Section: Observational Evidence Of Vertical Pumping In Barrow Canyonmentioning
confidence: 99%